Immunophenotypic features of leukemic stem cells and bulk of blasts in acute myeloid leukemia - Ivanivska, T.S.; Sklyarenko, L.M.; Zavelevich, M.P.; Philchenkov, A.A.; Koval, S.V.; Polishchuk, A.S.; Gluzman, D.F. (PH Akademperiodyka, 2023)
Summary. According to the modern concept, leukemic stem cells (LSC) in acute myeloid leukemia (AML) are distinct from the bulk of leukemic cells in bone marrow and peripheral blood of AML patients. Nevertheless, LSC are responsible for managing all the hierarchy of the bulk of leukemic blast populations. This mini-review provides brief information on the distinctive features of LSC and blast cells in cytologically recognized types of AML. The study of different phenotypes of LSC and blast cells in AML with the aid of up-to-date flow cytometric techniques is important both for the deep insight into the mechanisms of leukemogenesis and development of novel strategies of target therapy. The urgent need for extending the diagnostic panel of monoclonal antibodies used for diagnosing AML is beyond doubt.